OPTIMASI FORMULASI NORI BROKOLI DENGAN MENGGUNAKAN PROGRAM DESIGN EXPERT METODA MIXTURE D-OPTIMAL - thomas gozaly (Pasundan Food Technology Journal (PFTJ), 2018)
The purpose of this research was to obtain the optimal formulation of making nori broccoli with Design Expert program using the D-Optimal method. This research was conducted to produce characteristic of chemical, physics, and organoleptic in accordance with the desire so that generated the selected formulation. The response in this research was chemical analysis of water content, fiber content and vitamin C content, physics response is tensile strength test, and organoleptic test with attributes of color, flavor,texture, and taste. The result of this research was obtain 11 formulation offered for produce one optimal formulation (selected) based on desirability value 0,825 was broccoli 70%, water 16,50%, carrageenan 3%, and other additional materials as fixed variable consist of sesame oil 2,9%, salt 1,4%, sugar 3,3%, dried ebi 2%, and glycerol 0,9%. The selected sample has conducted an analysis of antioxidant activity and tensile strength test. The results of laboratory analysis against water content 12,63%; fiber content 11,44%; vitamin C content 5,38%; organoleptic test attribute of taste 3,60; texture 4,20; flavor 3,80; and color 4. The results of laboratory analysis approach of design expert program prediction method of d-optimal. For the result of antioxidant activity in raw material was 239,485 ppm and product was 8031,786 ppm and the average result of tensile strength test in the product was 129,68 kPa.